Bisnis Transportasi dalam Pusaran Globalisasi - Mutimatun Ni’ami (Faculty of Law, Universitas Pekalongan, 2020)
This study aims to examine the differences between conventional taxis and online taxis and whether the existing legal regulations are sufficient to regulate the two modes of transportation. The author's curiosity comes from seeing the past when taxis were considered a luxury means of transportation that people rarely use except for emergencies, so city buses and public transportation become the choice of citizens. The choice that was